Supporting Female Students’ Listening Ability through English Study Club : A Comparative Study - Novi Dwi Yuliani; Muhammad Rifqy Rujani (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2022)
This research wants to know a comparation between the students who join and who do not join English study club in their listening ability at Darul Hijrah Islamic Boarding School for female. This research also provides information regarding the implementation of English study club for supporting female students’ listening ability. Furthermore, the researcher also wants to find out what are the factors that make their listening ability are different. The data are collected through observation, interview, test and documentary and uses quantitative method. The result of this research states that there is a significant difference between the students who join and who do not join English Study club. The value of to is 2,76 that’s higher than the value in significance 5% that is 2,05. So,  2,67 > 2,05. The factors that help student’s who join English Study Club to have a better score in listening abiliy, such as : Encourage students to listen as often and as much as possible, Help Students Prepare to Listen, Once may not be enough, Encourage students to respond to the content of a listening,and Different listening stages demand different listening tasks.